Relatório de estágio técnico profissional em medicina veterinária: anestesiologia de pequenos animais - Scopel, Gabriel da Silva (2023)
The Professional Technical Internship (ETP) represents the final phase of the academic journey in Veterinary Medicine, offering the opportunity to apply the knowledge acquired throughout the course in an area of ​​interest for future professional practice. The ETP was conducted in the area of ​​Small Animal Anesthesiology, under the guidance of Prof. Dr. Renan Idalencio, at the Veterinary Hospital of the University of Passo Fundo (HV-UPF), under the supervision of Veterinarian Luís Henrique Bedendo, during the period from August 2nd to October 31st, 2023, totaling 494 hours. During the internship, it was possible to immerse myself in the routine of the surgical suite of a university hospital and play an active role, assisting veterinary anesthesiologists in various procedures, including administering medications and evaluating patients. Furthermore, when there were no surgeries, clinical consultations, imaging exams and sample collection for laboratory analysis were attended. This report details the context of the internship, describes the comprehensive activities carried out and presents information about the anesthetic procedures and protocols followed. To facilitate understanding, the case series is arranged in tables and at the end an anesthetic case report. The ETP represented an invaluable learning experience, contributing significantly to personal and professional growth. It allowed us to obtain a comprehensive understanding of the dynamics in the surgical suite, promoted constructive interactions with colleagues and experienced professionals and prepared us more solidly to face the challenges of the job market.